D. H. Lawrence’s Theology of the Body: Intersections with John PaulII’s Man and Woman He Created Them - Boone, N. S. (Religion and the arts, 2014)
This article examines the philosophical foundations of both D. H. Lawrence’s sexual ethics and the “theology of the body” developed by Pope John Paul II. Although Lawrence is often viewed, rightly in most cases, as a critic of Christianity, and even though his work has been scorned or outright banned by Christian groups over the years, Lawrence’s overarching view of life in his later years was remarkably amenable to Catholic Christianity. Linking Lawrence with Christian and even Catholic thought is not unique, as two books from the 1950s make claims very similar to mine. But these critical works are almost six decades past, and this article primarily contributes to this earlier criticism by aligning Lawrence with the theology of sexuality developed by Pope John Paul II. Though the Pope and Lawrence do differ on some points, they do not differ substantially in their philosophical stances regarding the mind/body relationship or the absolute necessity of full reciprocity in sexual intercourse. This essay does not claim that Lawrence was a Catholic, or even a Christian, or that if he had lived longer he would have converted to Catholicism. In his own mind, he had made a clean break with Christianity. But as some of his late essays extol the virtues of the Catholic Church’s development of the sacrament of marriage, Lawrence may not have been surprised to see how thoroughly his thoughts on sex and marriage align with those of the late Pope.